Exploration of bioactive compounds and antibacterial activity of marine blue-green microalgae (Oscillatoria sp.) isolated from coastal region of west Malaysia - Bhuyar, Prakash; Mohd Hasbi, Ab Rahim; Maniam, Gaanty Pragas; Ramaraj, Rameshprabu; Govindan, Natanamurugaraj (Springer Nature Switzerland, 2020)
Cyanobacteria is blue–green microalgae that produces a variety of secondary metabolites such as antibiotic, cytotoxic and antimicrobial agents. Present investigation proposed to study an extraction of active agents from Cyanobacteria and its antibacterial activity. The Cyanobacteria were collected, and isolated colony was found to be Oscillatoria sp. and it was grown in BG 11 medium for mass cultivation. Then the centrifuged biomass was weighed and used for extraction of bioactive compounds. GCMS analysis from Oscillatoria sp. determines fatty acid, triazine derivatives, pyridine derivatives, acridine derivatives. The result revealed that Oscillatoria sp. can play crucial roles as antibacterial agents because the methanolic extract are inhibiting the growth of S. aureus for gram-positive whereas P. aeruginosa for gram-negative bacteria. The crude extract was effective against S. aureus with the highest concentration, 100 mg/ml where area of the zone was 14.10 ± 0.8 mm. The crude extract actively inhibited P. aeruginosa at 75 and 100 mg/ml with highest area of inhibition were in the average of 13.23 ± 0.1 and 15.43 ± 0.2 mm. Finally, the antimicrobial activity was carried out by disc diffusion method with different concentrations of active compounds shows the MIC value in gram-positive bacteria was 30 µg/ml whereas for gram-negative bacteria was 25 µg/ml. Cyanobacteria extract should be preferred and considered to be new natural drug or antibiotics in pharmaceutical and health care industry. This coastal region should be studied further by researchers to study more information and benefits in the future.